Analysing Cholera-Measles Epidemics of a Fractional-Order Model with Preventive Strategies Using Laplace Adomian Decomposition Method - Olaosebikan, Mutiu Lawal; Oladapo, Asimiyu Olalekan; Ogunniran, Muideen Odunayo (Program Studi Matematika, Universitas Nusa Cendana, 2026)
This study provides an in-depth examination of cholera-measles epidemics through a fractional-order mathematical model that integrates essential preventive measures. By employing fractional calculus, the model captures the memory and hereditary properties of disease transmission dynamics, offering a more realistic representation than classical integer-order models. This consists of multiple compartments representing the progression of each disease, with control measures such as treatment, vaccination, water sanitation and public health awareness integrated into the system. Considering numerical iteration on model to see how these changes affect the spread of disease. The results reveal that fractional-order models not only enhance the accuracy of epidemic forecasting but also demonstrate the effectiveness of timely and combined preventive strategies in reducing infection rates. Sensitivity analysis further identifies crucial parameters influencing disease dynamics, guiding resource allocation for optimal control. The findings indicate the relevance of fractional modeling and provides valuable insights for informing strategic planning efforts to curb cholera-measles transmission.